Etika Mengkritik Penguasa dalam Al-Qur’an: Kontekstualisasi Penafsiran Gus Baha’ atas ‎Kisah Nabi Musa di Konten Youtube - Zayyadi, Ach.; Rofiah, Hofidatur; Ainy, Qurrotul (Universitas Islam Negeri Imam Bonjol Padang, 2024)
This research originates from and departs from complaints, criticism and comments from many groups in Indonesia towards a leader, which nowadays can be conveyed by anyone in various ways without being bound by space and time. Therefore, many of the criticisms conveyed differ from the methods taught by Islam. What is the proper ethics in criticizing the government according to the Qur'an? One interesting thing to discuss and can be the answer to the question above is how the Prophet Musa criticized Pharaoh, which was later enshrined in QS. Thaha [20]: 44. This article aims to discover how to convey criticism of good rulers using the proper ethics by the rules of the Qur'an, which is based on the contextualization of Gus Baha's interpretation on the YouTube Channel. This research was conducted using qualitative methods with a library research approach. All data was sourced from written and documented materials in videos and written references. The presentation of the data uses a descriptive-analysis method by describing the problems in the research and then analyzing and presenting the results using content analysis very carefully so that they can provide optimal answers to the problems being researched. The end of this study concludes that based on the contextualization of Gus Baha's interpretation of QS. Thaha [20]: 44 finally came up with an ethical formulation criticizing the authorities, namely, 1) by choosing an effective and targeted language (qaulan layyinan); 2) gradually; and 3) in the right situation.